Toward an Integrative Model of Research and Practice in Counsellingd - Lecompte, Conrad; Bernstein, Bianca L. (Canadian Journal of Counselling and Psychotherapy, 2012)
A model of communication is offered in response to the need for a meaningful conceptual framework generating representative, systematic, and integrated research in counselling and counsellor training. The usefulness of the communication paradigm for the practitioner and counsellor educator in their conceptualization of the counselling and training process at molar and molecular levels, for the theorist in the study of different counselling approaches, and for the researcher in the formulation of problem, hypotheses, and design, is explored. The specification and systematic study of the complex interactions among the identified variables is intended to facilitate the development of consistently effective counselling and training strategies by counselling researchers and practitioners.